The impact of different warm-up strategies on acceleration and deceleration demands in highly trained soccer players - Silva, H.; Nakamura, F. Y.; Bajanca, C.; Pinho, G.; Loturco, I.; Marcelino, R. (European Journal of Sport Science, 2024)
This study compared the differences in acceleration and deceleration demands between three different warm-up (WU) strategies (Reaction speed [exercises with reaction to a stimulus], Run [self-paced running], and Speed [exercises such as shuttle running or circuits]) applied to highly trained soccer players. Nineteen players were monitored for 4 weeks using a 10 Hz Global Positioning System. Accelerations and decelerations magnitudes were classified as low (25%-50%), moderate (50%-75%), and high (>75%) intensities. Additionally, efforts were analyzed according to their respective starting speeds (<5, 5-10, 10-15, 15-20, 20-25, and >25 km h-1). Differences between WU strategies were estimated via paired mean differences along with effect sizes. The three WU strategies led to few efforts starting >15 km h-1 and high-intensity efforts (<1 effort per minute). Players performed more high-intensity accelerations during Speed than Reaction Speed (ES: 0.74 [90% CI: 0.21, 1.33]); more moderate-intensity accelerations during Reaction Speed than Run (ES: 1.29 [90% CI: 0.72, 2.00]); more moderate-intensity decelerations during Reaction Speed than Run (ES: 0.64 [90% CI: 0.04, 1.32]) and Speed (ES: 0.89 [90% CI: 0.37, 1.50]); more decelerations started at 20-25 km h-1 during Speed than Reaction Speed (ES: 0.81 [90% CI: 0.20, 1.49]) and Run (ES: 0.76 [90% CI: 0.42, 1.18]); and more decelerations started at >25 km h-1 during Speed than Reaction Speed (ES: 3.57 [90% CI: 2.88, 4.58]). In conclusion, Speed elicited higher acceleration and deceleration demands than the Reaction Speed and Run WU strategies, and this should be considered when designing training sessions.